The Development of Learning Activities Linking Life Skills and Bio Circular Green Economy (BCG) in Biology Subjects for High School Students of Mahasarakham University Demonstration School (Secondary), Thailand - Wutthisak Bunnaen; Nichapat Jirapangoonrachat; Nathamon Sangsaikaew; Phanat Phothibat; Wittaya Worapun; Autthapon Intasena (IJCAR: Indonesian Journal of Classroom Action Research, 2026)
This research focuses on the development of learning activities that integrate life skills and the Bio-Circular-Green Economy (BCG) concept within the biology curriculum for upper secondary students at the Mahasarakham University Demonstration School (Secondary). The objectives of the study were to develop learning activities, enhance students’ reflective thinking processes, promote their self-development, and assess student performance. The target group consisted of Grade 10 students from classes 4/1 and 4/2. The classroom action research methodology was employed, integrated with the Professional Learning Community (PLC) model, referred to as the Professional Learning Community Classroom Action Research (PLC-CAR). The research found that the comparison of the mean scores of students’ reflective thinking skills between Group 1 and Group 2 showed a statistically significant difference at the .05 level. However, the comparison of mean scores for student performance evaluation in specific areas between the two groups showed no significant difference. Similarly, the analysis of the mean scores of students’ self-assessment indicated no significant difference between the two groups, with both groups reporting a high level of self-assessed performance. In conclusion, the learning activities developed to integrate biology content with life skills and the BCG economic model effectively encouraged students to engage in self-directed learning, collaborate with others, develop reflective thinking abilities, and apply knowledge for personal and community benefit. These outcomes align with the principles of effective 21st-century learning.